Differential expression of soluble pyrophosphatase isoforms in Arabidopsis upon external stimuli - Öztürk Gökçe, Zahide Neslihan; Greiner, Steffen; Rausch, Thomas (Turkish journal of botany, 2015)
In plants, pyrophosphate (PPi), generated in a wide range of reversible anabolic reactions, is hydrolyzed by pyrophosphatases. The presence of tonoplast- and Golgi-integral H+-translocating pyrophosphatases in plants led to the conclusion that plant cytosol has no soluble pyrophosphatase activity. However, the Arabidopsis thaliana (L.) Heynh. genome also encodes five soluble pyrophosphatase isoforms (PPas). There are almost no data in the literature on their redundancy in plant metabolism; therefore, we performed expression analyses of A. thaliana soluble pyrophosphatase isoforms in response to external stimuli including carbohydrate status, hormone action, and stress exposure. The results revealed pronounced specificity for each isoform. Interestingly, one isoform (PPa3; At2g46860) was specifically induced during seedling etiolation, and in the presence of the nonmetabolizable sugar 3-O-methylglucose. Based on quantitative PCR analyses, PPa1 (At1g01050) and PPa4 (At3g53620) appeared to be regulated by sugars. Quantitative PCR analyses indicated isoform- and tissue-dependent responses of PPa isoforms to ABA, salt, and cold stresses. PPa2 At2g18230 and PPa5 (At4g01480) responded differentially to salinity, cold treatment, and ABA. We conclude that plant cytosolic pyrophosphatases perform multiple, so far overlooked functions during plant development and stress exposure.
Gesehen am 26.06.2020